Business and public health impacts of a food safety rating program among pork vendors in Vietnam - Ambler, Kate; Murphy, Mike; Sinh Dang-Xuan; Hoffmann, Vivian; Trang Le-Thi-Huyen; Unger, Fred; Vuong Bui-Nghia; Huong Pham-Thi; Duy Nguyen-Quang; Hung Nguyen-Viet (International Livestock Research Institute, 2024)
Ninety percent of pork, the most widely consumed meat in Vietnam, is sold through wet markets, where hazards are pervasive.